Robot system reliability and safety a modern approach - Dhillon, B. S. (Balbir S.), 1947- (CRC Press, 2015)
As robots are used more and more to perform a variety of tasks in a range of fields, it is imperative to make the robots as reliable and safe as possible. Yet no book currently covers robot reliability and safety within one framework. Robot System Reliability and Safety: A Modern Approach presents up-to-date information on robot reliability, safety, and related areas in a single volume, eliminating the need to consult diverse sources. After introducing historical, mathematical, and introductory aspects, the book presents methods for analyzing robot system reliability and safety.